Obozy koncentracyjne jako nowoczesna forma zwalczania przestępczości w Republice Federalnej Niemiec? - Fikus, Sebastian (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The problem of participation of the Nazi elites in the structures of the German Federal Republic is increasingly engaging for German historians. Popular, non-academic works also address the issue of joining the police force by former officials of the Third Reich. However, in the German texts it is consistently stressed that Nazi elites did not influence the social and political life of the German Federal Republic. Nevertheless, the debate on reintroducing concentration camps shows the high standing of national socialism ideology long after World War II.
Keywords: Nazistowscy urzędnicy ścigający nazistowskich zbrodniarzy wojennych; obozy koncentracyjne; policja kryminalna Gestapo; powojenne Niemcy; Adenauer, Konrad (1876-1967)